On the unipotence of autoequivalences of toric complete intersection Calabi-Yau categories - Herbst, Manfred; Walcher, Johannes (Arxiv, 2009)
We identify a class of autoequivalences of triangulated categories of singularities associated with Calabi-Yau complete intersections in toric varieties. Elements of this class satisfy relations that are directly linked to the toric data.
Gesehen am 25.02.2020